Sintered flux and method suitable for hydrogen conveying submerged-arc welding steel pipe
By optimizing the chemical composition and proportion of flux, welds with high melting point and low diffusion of hydrogen are formed, which solves the problem that existing fluxes are difficult to control the hydrogen content of welds in hydrogen transport pipeline welding, and achieves high strength and low welds Risk of hydrogen embrittlement.
Patent Information
- Application Number
- CN202310911046.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-07-24
AI Technical Summary
During the welding process of existing fluxes, it is difficult to effectively control the diffused hydrogen content in the weld, resulting in the weld being prone to hydrogen embrittlement, which increases the safety hazards of the pipeline.
Using a new sintering flux, its chemical compositions include HJ431 solder powder, MgO, CaF2, BaCO3, TiO2, Al powder deoxidizer and Mn-Fe alloy agent, by optimizing the proportion and particle size of these components, it forms a high melting point and Low-diffusion hydrogen welds.
The high strength, excellent impact toughness and low diffusion hydrogen content of the weld are achieved, which significantly reduces the risk of hydrogen embrittlement and ensures the safety and stability of the pipeline.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of pipeline welding, and particularly relates to a sintered flux and a method for submerged arc welding steel pipes suitable for hydrogen transportation. Background Art
[0002] Pipeline transportation is an indispensable way to transport hydrogen on a large scale and over long distances. Compared with the economic radius of 150km for long-tube trailers, pipeline hydrogen transportation can easily achieve hydrogen transportation of more than 200km, and the amount of hydrogen transported by liquid hydrogen is also much smaller than that by pipeline. Under normal circumstances, pure hydrogen pipelines can achieve a hydrogen transport capacity of 100 tons / day, which can efficiently and quickly meet the application of downstream hydrogen-end industries. As a gas molecule, hydrogen is extremely small, colorless and odorless. Compared with natural gas, it has the characteristics of low density and large diffusion coefficient. For general pipes, long-term contact with hydrogen will enter the internal defects of the metal material structure and cannot diffuse out, which can easily cause the plasticity and strength of the metal material to decrease, leading to material cracking, and serious degradation of mechanical properties, causing brittle fracture, that is, the "hydrogen embrittlement" phenomenon. For the welding of steel pipes for hydrogen transmission pipelines, the internal organizational state, structure and free diffused hydrogen of the weld will have a great influence on the sensitivity to hydrogen embrittlement, especially the number, shape, size and distribution of internal inclusions are particularly significant in inducing hydrogen embrittlement fracture. At the same time, elements such as C, Mn, Si, S, P, etc. that are easy to harden and contaminate the weld will also increase the probability of "hydrogen embrittlement" in the weld after pipe welding. Under excessively high pressure, the hydrogen embrittlement and hydrogen-induced cracking of the weld of the required high-strength material will be more obvious, so the pipes used for transporting hydrogen medium are preferably low-grade steel pipes, and higher requirements are placed on the purity, organizational morphology and internal hydrogen ion content of the weld.
[0003] Most of the pipes for high-pressure hydrogen energy transportation are produced by submerged arc welding. The main means of controlling [H] in the weld is the reasonable selection and matching of welding materials during the welding process. Sintered flux is an auxiliary material that is responsible for isolating harmful gases from the outside air from penetrating and metallurgical chemical reactions of slag and weld pool during submerged arc welding. A large number of production practices and related studies at home and abroad have proved that the main source of the increase of internal free hydrogen ions and inclusions is the flux material. Therefore, the most effective measure to reduce the hidden danger of hydrogen damage in pipes from the source is to optimize the relevant components in the sintered flux to achieve the dissolution and control of residual [H] in the weld during the metallurgical chemical reaction of the flux. The Mn, Si and C contents in the conventionally used SJ101 and SJ301 fluxes are often too high, and the P and S content control requirements are too loose. There are no strict requirements for diffusible hydrogen. If directly applied to the welding of hydrogen-resistant pipeline steel, it is very easy to cause segregation and inclusion in the weld, resulting in increased hydrogen embrittlement sensitivity of the steel pipe weld, and ultimately causing a major safety hazard to the hydrogen pipeline steel pipe; and the commonly used special low-hydrogen sintering flux on the market is mainly produced by improving the quality of raw materials, reducing the crystallized hydrated substances in the flux, optimizing the sintering temperature and protective measures in the preparation process on the basis of the conventional fluorine-alkali slag system. There are often problems such as high raw material and production costs, inability to effectively control the diffusible hydrogen in the weld, and low welding speed, which seriously restricts the large-scale production and application of hydrogen energy transportation pipes. Therefore, it is necessary to develop a low-cost and high-speed sintering flux suitable for hydrogen transportation submerged arc welding steel pipes for hydrogen-resistant pipeline steel. At present, there are many patents on low-hydrogen sintered fluxes in the prior art. Among them, the searched patents include: an ultra-low diffusible hydrogen sintered flux for low-temperature steel welding and its preparation and application (publication number: CN 108581273A). This patent mainly adopts a fluorine-alkali slag system, and achieves the purpose of removing hydrogen and improving performance through a variety of different component ratios. The addition of raw materials to the flux is complicated and the price is too high; high-alkalinity, high-toughness, low-hydrogen sintered flux and its preparation method (publication number: CN 102601544A). This patent has a relatively broad control on P and S inclusions in the flux, which is not conducive to the safety requirements of pipeline hydrogen transportation; sintered flux for hydrogen-resistant steel and its preparation method, as well as deposited metal (publication number: CN 112496596A), in which a certain amount of HJ431 smelting flux slag and a large amount of chemical components after welding are added to achieve the low hydrogen requirement. The MnO and SiO2 in the HJ431 slag added by the flux combine with FeO to form a complex and S, P compounds that are very likely to form inclusions in the weld, which can easily cause the purity of the weld to decrease, posing a safety hazard to pipeline hydrogen transportation. Summary of the invention
[0004] In view of the above problems, the purpose of the present invention is to provide a sintered flux and method for submerged arc welding steel pipes suitable for hydrogen transportation. The sintered flux of the present invention is combined with H08MnNi2A submerged arc welding wire to be applied to hydrogen-resistant pipeline steel for high-speed submerged arc welding at 1.6 m / min. The weld has moderate tensile strength, excellent impact toughness, low diffusible hydrogen content, and HIC and SSCC corrosion resistance consistent with the corresponding hydrogen-resistant base material. The good performance can effectively solve the problems of efficient welding, toughness and pipeline hydrogen energy transportation safety of pipeline steel.
[0005] The technical solution of the present invention is: a sintered flux suitable for hydrogen transport submerged arc welding steel pipe, the chemical composition of the sintered flux is as follows by weight percentage: HJ431 welding powder: 40-50%, MgO: 10-15%, CaF2: 15-20%, BaCO3: 5-10%, TiO2: 2-5%, Al powder deoxidizer: 1-3%, Mn-Fe alloying agent: 5-10%, P<0.02%, S<0.018%.
[0006] The particle size of the HJ431 welding powder is 80-100 meshes, and the MnO content in the HJ431 welding powder is more than 40%; the CaF2 is added in the form of fluorite mineral powder, the particle size of the fluorite mineral powder is more than 100 meshes, and the CaF2 content of the fluorite mineral powder is 98%; the MgO is added in the form of fused magnesia, the particle size of the fused magnesia is 80-100 meshes, and the MgO content of the fused magnesia is 99%; the TiO2 is added in the form of natural rutile, the particle size of the natural rutile is 80-100 meshes, and the TiO2 content of the natural rutile is 93%; the BaCO3 is added in the form of barium carbonate, the particle size of the barium carbonate is 100-120 meshes, and the BaCO3 content in the barium carbonate is 99.2%; the particle size of the Al powder deoxidizer is 60-80 meshes, and the Al content of the Al powder deoxidizer is 99%; the particle size of the Mn-Fe alloying agent is 60-80 meshes, The Mn content of the Mn-Fe alloy is 99%.
[0007] When the chemical components required for the sintering flux are added in the form of HJ431 welding powder, fluorite mineral powder, fused magnesia, natural rutile, barium carbonate, Al powder deoxidizer, and Mn-Fe alloying agent, the weight percentages of the mineral components and alloys in the sintering flux are: HJ431 welding powder: 40-50%, fluorite mineral powder: 12-24%, fused magnesia: 12-18%, barium carbonate: 7-12%, natural rutile: 2-5%, Al powder deoxidizer: 3-5%, and Mn-Fe alloying agent: 5-10%.
[0008] The Mn-Fe alloying agent is an electrolytic Mn-Fe alloying agent.
[0009] The moisture content of the sintered flux is less than 0.1%, the mechanical inclusions in the sintered flux is less than 0.3%, the tensile strength of the weld welded with the sintered flux is 485-517MPa, the -10°C girth weld impact energy is ≥100J, the toughness transition temperature is below -40°C, the -10°C CTOD fracture toughness σm is ≥0.254mm, and the diffusible hydrogen content is ≤4ml / 100g.
[0010] The chemical composition of the above-mentioned sintered flux for hydrogen transport submerged arc welding steel pipe is selected based on: (1) BaCO3 is an alkaline oxide. BaCO3 is added to HJ431. The CO2 produced after decomposition makes the weld pool form gas-slag joint protection during the welding process, reduces the partial pressure of hydrogen in the arc atmosphere, and inhibits the diffusible hydrogen content in the cladding metal. It greatly improves the basicity of the slag, improves the impact toughness of the cladding metal, and enhances the crack resistance of the weld deposited metal. When the BaCO3 content is less than 5%, gas protection cannot be formed, and its effect on the weld is not obvious; however, when the BaCO3 content exceeds 10%, the amount added is too much, and too much gas will be released during submerged arc welding, which is easy to produce too much smoke, reducing the protection effect of the slag, and the generated CO bubbles are very easy to form pressure pits on the weld surface. At the same time, the excessive smoke generated is not conducive to environmental protection. Therefore, it is necessary to control BaCO3 within 5-10%; (2) MgO is an alkaline oxide and a high-melting-point oxide with a melting point of 2800°C. On the basis of the HJ welding powder components added, it increases the alkalinity of the slag, reduces the viscosity of the acidic slag, increases the permeability of the slag and reduces the diffusible hydrogen content. At the same time, during the welding process, it increases the melting temperature of the flux slag, reduces the melting rate, and reduces the amount of slag, thereby achieving a good adjustment effect on the process performance of the weld. When the added MgO content is less than 10%, the overall MgO content in the flux is too little, and the effect of increasing the slag melting point is not obvious, resulting in excessive slag generated during welding, which is easy to cause irregular and unsightly weld edges. When the added MgO content is less than 15%, the overall high-melting-point component content in the slag is too high, and the slag solidifies prematurely during welding, making it impossible for the reaction in the weld metal to fully proceed, which is very easy to cause weld pits and cannot be spread freely. In view of this, the MgO content needs to be controlled at 10-15%; (3) CaF2 is an alkaline salt. As an important component of dehydrogenation in flux, it has a small surface tension and a low melting point. It can effectively dilute the flux melt during welding. Under high-temperature arc, CaF2 is relatively active and can react with SiO2 to generate SiF4 gas, which can remove hydrogen from the arc zone, thereby preventing hydrogen from dissolving in the metal, thereby reducing the hydrogen content in the weld. CaF2 also has a good effect on metal desulfurization, and can effectively reduce the oxygen content of weld metal, improving the plasticity and impact toughness of the weld. However, excessive CaF2 has a destructive effect on potassium and sodium ions in the arc cavity atmosphere, causing instability in the submerged arc welding arc. In addition, it will over-dilute the slag and affect the weld formation and slag removal. At the same time, the fluoride gas generated during welding will cause great harm to the human body. Therefore, the CaF2 content needs to be controlled at 15~20%.
[0011] (4) TiO2 is added mainly to improve the weld morphology and arc stability on the basis of the added HJ431 welding powder, and at the same time achieve the purpose of transitioning Ti elements into the weld. TiO2 can reduce surface tension when in liquid state, and can rapidly increase surface tension during cooling. However, when added in large amounts, the slag will become significantly thinner, the slag shell will become harder, and the permeability of the slag will be reduced. Since the added HJ welding powder contains more than 5% TiO2, when the TiO2 content in the flux exceeds 5%, the surface energy tension of the slag will be too large, the slag will be too thin, and the slag removal after welding will be reduced. The process performance of the weld will deteriorate, and the weld will not have the expected protective effect. However, if TiO2 is not added, the addition of a single MgO substance will make the melting point of the slag too high, reducing the coverage of the slag on the weld metal. In view of this, the TiO2 content in the flux should be limited to 2~5%; (5) Al powder deoxidizer and Mn-Fe alloying agent. Al has a greater affinity for oxygen and can reduce the excess coefficient of hydrogen in iron. At the same time, it can improve the corrosion resistance of the weld to a certain extent. Al is easily oxidized. When used in combination with Mn, it will combine with O2 at the front end of the arc in advance during the welding process to protect and promote the transition of Mn elements to the weld metal. It can improve the weld structure, refine the pearlite grains, increase the weld strength and hardness, and reduce the brittle transition temperature. At the same time, it can also desulfurize and reduce the sensitivity to hot cracks. In order to obtain high strength and low-temperature toughness, the content of Al powder deoxidizer and Mn-Fe alloying agent in the flux of the present invention is controlled at 1-3% and 5-10%.
[0012] (6) P and S are impurity elements. S and iron are infinitely soluble in liquid state, and are easily distributed in austenite Fe+FeS eutectic, causing hot brittleness of welds, resulting in a sharp decrease in weld plasticity and toughness; P is widely present in the form of phosphide, which aggravates hydrogen corrosion, but at the same time phosphorus can improve the corrosion resistance of steel. When the phosphorus content is too high, it will cause cold brittleness and deteriorate the toughness of steel, so its content is controlled at P≤0.015%; S≤0.010%; A method for preparing a sintered flux for hydrogen transport submerged arc welding steel pipe as described above comprises the following steps: S1: By weight, 40-50 parts of HJ431 welding powder, 12-18 parts of fused magnesia, 7-12 parts of barium carbonate, 18-24 parts of fluorite mineral powder, 2-5 parts of natural rutile, 3-5 parts of Al powder deoxidizer, and 5-10 parts of Mn-Fe alloying agent are uniformly mixed; S2: adding 15.48-31.5 parts of a binder to the mixture obtained in step S1, and vibrating and shaking the wet material formed by the bonding with a dustpan or a granulator to granulate; S3: During the granulation process, the particle size of the granulated flux is controlled between 10 and 60 meshes through a 10-20 mesh sieve; S4: drying the formed flux in a high temperature furnace at a temperature range of 200-350°C; S5: sintering the dried flux in a sintering furnace at a temperature range of 800-900°C; S6: The sintered flux is screened through 10~60 mesh and then packaged.
[0013] The binder in step S2 is potassium sodium water glass, and the potassium sodium water glass as a binder has a Baume degree of 41.9-43.9 and a modulus of 2.5-2.7.
[0014] The technical effects of the present invention are as follows: 1. The present invention introduces CaF2 into the chemical composition of the sintered flux, which can effectively dilute the flux melt during the welding process; under high-temperature arc, CaF2 is relatively active and can react with SiO2 to generate SiF4 gas, which can remove hydrogen from the arc zone, thereby preventing hydrogen from dissolving in the metal, thereby reducing the hydrogen content in the weld. 2. The present invention introduces Al powder deoxidizer and Mn-Fe alloying agent into the chemical composition of the sintered flux by adding corresponding Al powder deoxidizer and Mn-Fe alloying agent to the flux, thereby reducing the oxidation ability of the slag and reducing harmful gases and impurities in the slag. During the welding process, the flux assists the transition Mn alloy to play a good fine grain role, which promotes the acquisition of a large amount of refined and uniform acicular ferrite structure in the weld metal, ensuring that the weld has excellent process and mechanical properties and HIC and SSCC corrosion resistance on the basis of high strength and toughness and stable quality, thereby improving the purity of the weld. 3. The tensile strength of the weld welded by the sintered flux of the present invention is 485-517MPa, the impact energy of the girth weld at -10°C is ≥100J, the toughness transition temperature is below -40°C, the -10°C CTOD fracture toughness m≥0.254mm, and the diffusible hydrogen content is ≤4ml / 100g. DETAILED DESCRIPTION
[0015] Example 1 A sintered flux suitable for hydrogen transport submerged arc welding of steel pipes, the chemical components of the sintered flux are as follows by weight percentage: HJ431 welding powder: 40-50%, MgO: 10-15%, CaF2: 15-20%, BaCO3: 5-10%, TiO2: 2-5%, Al powder deoxidizer: 1-3%, Mn-Fe alloying agent: 5-10%, P<0.02%, S<0.018%.
[0016] The particle size of the HJ431 welding powder is 80-100 meshes, and the MnO content in the HJ431 welding powder is more than 40%; the CaF2 is added in the form of fluorite mineral powder, the particle size of the fluorite mineral powder is more than 100 meshes, and the CaF2 content of the fluorite mineral powder is 98%; the MgO is added in the form of fused magnesia, the particle size of the fused magnesia is 80-100 meshes, and the MgO content of the fused magnesia is 99%; the TiO2 is added in the form of natural rutile, the particle size of the natural rutile is 80-100 meshes, and the TiO2 content of the natural rutile is 93%; the BaCO3 is added in the form of barium carbonate, the particle size of the barium carbonate is 100-120 meshes, and the BaCO3 content in the barium carbonate is 99.2%; the particle size of the Al powder deoxidizer is 60-80 meshes, and the Al content of the Al powder deoxidizer is 99%; the particle size of the Mn-Fe alloying agent is 60-80 meshes, The Mn content of the Mn-Fe alloy is 99%.
[0017] When the chemical components required for the sintering flux are added in the form of HJ431 welding powder, fluorite mineral powder, fused magnesia, natural rutile, barium carbonate, Al powder deoxidizer, and Mn-Fe alloying agent, the weight percentages of the mineral components and alloys in the sintering flux are: HJ431 welding powder: 40-50%, fluorite mineral powder: 12-24%, fused magnesia: 12-18%, barium carbonate: 7-12%, natural rutile: 2-5%, Al powder deoxidizer: 3-5%, and Mn-Fe alloying agent: 5-10%.
[0018] The Mn-Fe alloying agent is an electrolytic Mn-Fe alloying agent.
[0019] The moisture content of the sintered flux is less than 0.1%, the mechanical inclusions in the sintered flux is less than 0.3%, the tensile strength of the weld welded with the sintered flux is 485-517MPa, the -10°C girth weld impact energy is ≥100J, the toughness transition temperature is below -40°C, the -10°C CTOD fracture toughness σm is ≥0.254mm, and the diffusible hydrogen content is ≤4ml / 100g.
[0020] Example 2 A method for preparing a sintered flux for hydrogen transport submerged arc welding of steel pipes as described above comprises the following steps: S1: By weight, 40-50 parts of HJ431 welding powder, 12-18 parts of fused magnesia, 7-12 parts of barium carbonate, 18-24 parts of fluorite mineral powder, 2-5 parts of natural rutile, 3-5 parts of Al powder deoxidizer, and 5-10 parts of Mn-Fe alloying agent are uniformly mixed; S2: adding 15.48-31.5 parts of a binder to the mixture obtained in step S1, and vibrating and shaking the wet material formed by the bonding with a dustpan or a granulator to granulate; S3: During the granulation process, the particle size of the granulated flux is controlled between 10 and 60 meshes through a 10-20 mesh sieve; S4: drying the formed flux in a high temperature furnace at a temperature range of 200-350°C; S5: sintering the dried flux in a sintering furnace at a temperature range of 800-900°C; S6: The sintered flux is screened through 10~60 mesh and then packaged.
[0021] The binder in step S2 is potassium sodium water glass, and the potassium sodium water glass as a binder has a Baume degree of 41.9-43.9 and a modulus of 2.5-2.7.
[0022] Example 3 According to the sintered flux for hydrogen transport submerged arc welding steel pipe described in Example 1, the preparation method of the sintered flux for hydrogen transport submerged arc welding steel pipe described in Example 2 is used to prepare the sintered flux. The specific process is as follows: (1) Flux components When the chemical components required for the sintering flux are added in the form of HJ431 welding powder, fused magnesia, barium carbonate, fluorite, rutile, aluminum iron, and electrolytic manganese iron, the weight percentages of mineral components and alloys in the sintering flux are: HJ431 smelting welding powder: 47.6%; fluorite mineral powder: 18.8%; fused magnesia: 12.4%; barium carbonate: 7%; natural rutile: 6%; aluminum powder deoxidizer: 2%; electrolytic Mn-Fe alloying agent: 6.2%.
[0023] (2) Preparation of sintered flux After the above-mentioned mineral components and alloys are mixed and stirred evenly, and the adhesive potassium sodium water glass is added for wet mixing, granulation is carried out with a dustpan or a granulator, and the particle size of the flux is controlled between 10 and 60 meshes. After that, it is dried at a low temperature of 200 to 250°C, and then sintered at a high temperature of 800 to 900°C. After being screened with a size of 10 to 60 meshes, it is packed into a moisture-proof packaging bag.
[0024] (3) The flux of the present invention is matched with the corresponding H08MnNi2A welding wire for weld metal welding. According to the relevant welding material standard requirements, the test plate is Q235, with a thickness of 25 mm, a groove angle of 20°, and a root gap of 15 mm. The welding specifications are current 480A, voltage 30V, welding speed 26m / h, interpass temperature 150±15°C, and the mechanical properties of the weld metal are shown in Table 1.
[0025] Table 1 Mechanical properties of deposited metal Sample No. <![CDATA[Yield strength σ s / MPa]]> <![CDATA[Tensile strength σ b / MPa]]> Elongation A / % <![CDATA[-10 °C impact toughness A kV / J]]> Diffusible hydrogen ml / 100g HY-01 420 525 22.0 <![CDATA[ 78、65、55、89、37 66]]> 3.77、3.28、3.31 HY-02 408 511 24.8 <![CDATA[ 68、77、43、83、40 63]]> 3.02、2.58、3.57 Standard requirements 390 490-670 18.0 ≥27 ≤4 It can be seen from Table 1 that when the flux of the present invention is matched with the corresponding low-temperature welding wire for deposited metal welding, compared with the standard requirements, the weld has higher strength and toughness and lower diffusible hydrogen content.
[0026] (4) The flux of the present invention is matched with H08MnNi2A welding wire to weld a steel pipe for hydrogen medium transportation, wherein the steel pipe has a steel grade of L360 / X52, a specification of Φ457×8.8mm, a chemical composition of C: 0.05, Si: 0.25, Mn: 1.18, P: 0.011, S: 0.0016, Nb: 0.07, Ni: 0.05, Cr: 0.02, Mo: 0.05, V: 0.05, Al: 0.03, and the rest is iron. The process used is: Y-type groove form, the lower groove angle is 80°, the root gap is 2mm, and the blunt edge is 5-6mm; the welding sequence is to use double-wire submerged arc welding to weld from the inside first, and then use single-wire submerged arc welding to weld from the outside of the steel pipe. Among them, the submerged arc welding process uses double wires for internal welding and single wire for external welding. The external welding current is 850A and the voltage is 30V. The internal welding front wire current is 680A and the voltage is 31.5V. The rear wire welding current is 480A and the voltage is 35V. The welding speed is 1.6m / min. The mechanical properties of the weld metal after welding are shown in Table 2.
[0027] Table 2 Mechanical properties of steel pipe weld metal Sample No. <![CDATA[Tensile strength σ b / MPa]]> Fracture location <![CDATA[-10°C Impact Toughness A kV / J]]> <![CDATA[CTODδ m / mm]]> 803384 489-524 Base Material 188、124、119139、147、157 <![CDATA[ 0.2662、0.2873、0.2655 0.2733]]> Standard requirements 460-760 Base Material ≥91 ≥0.254 As can be seen from Table 2, after the flux of the present invention is matched with the H08MnNi2A welding wire for submerged arc welding of the hydrogen medium transmission pipeline steel pipe, the weld has high toughness, and the weld slag does not flow during the welding process, the weld bead is regular, the weld surface is smooth, the metallic luster is obvious, the slag is easy to fall off, and the tensile strength of the weld metal meets the requirements of the standard specification. After the steel pipe is welded by the flux of the present invention and the H08MnNi2A welding wire, after non-destructive testing according to the natural gas transmission pipeline welding standard, the weld has no cracks and excessive pores, and the slag inclusions meet the standard requirements, and the weld has excellent fracture toughness.
[0028] According to the sintered flux for hydrogen transport submerged arc welding steel pipe described in the above-mentioned Example 1, the sintered flux is prepared by the preparation method of a sintered flux for hydrogen transport submerged arc welding steel pipe described in Example 2, and the same flux use process as in Example 3 is adopted. The specific situation is as described in Example 5, Example 6, Example 7, and Example 8. The comparative examples are Comparative Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4.
[0029] The chemical element compositions of the sintered fluxes in Examples 4 to 7 and Comparative Examples 1 to 4 are shown in Table 3 in terms of weight percentage.
[0030] Table 3 Chemical element composition of sintered flux in Examples 4 to 7 and Comparative Examples 1 to 4 by weight percentage (wt%) Serial number HJ431 welding powder <![CDATA[CaF2]]> MgO <![CDATA[BaCO3]]> <![CDATA[TiO2]]> Al Mn P S Example 4 41.1 18.7 14.9 9.3 4.6 2.6 8.8 0.018 0.015 Example 5 44.6 17.5 14.1 8.8 4.9 2.5 7.6 0.019 0.017 Example 6 43.8 19.5 13.6 9.8 3.8 3.0 6.5 0.017 0.018 Example 7 49.5 17.8 12.8 7.4 2.8 3.0 6.7 0.015 0.018 Comparative Example 1 38.9 19.5 15.5 8.5 5.4 2.6 9.6 0.023 0.020 Comparative Example 2 50 18.9 14.8 8.5 4.8 3.0 -- 0.028 0.025 Comparative Example 3 51.8 15.4 13.8 6.5 5 -- 8.5 0.022 0.028 Comparative Example 4 49.3 21.3 12.2 7.8 -- -- 9.4 0.027 0.025
[0031] The mechanical properties of the girth welds welded with the sintered fluxes of Examples 4 to 7 and Comparative Examples 1 to 4 are shown in Table 5.
[0032] Table 5 Detection results of sintered fluxes and mechanical and process properties of girth welds of Examples 4 to 7 and Comparative Examples 1 to 4 Serial number Moisture content / % Mechanical inclusions / % Diffusible hydrogen content mL / 100g Tensile strength / MPa -10℃ impact value / J Toughness transition temperature / ℃ <![CDATA[CTODσ m / mm]]> Slag removal Spreadability Standard requirements ≤0.1 ≤0.3 ≤4 ≥460 ≥100 -- 0.254 Automatically fall off Smooth and beautiful Example 4 0.08 0.15 3.2 487 132-285 -40 0.287-0.306 Automatically fall off Smooth and beautiful Example 5 0.07 0.10 3.5 499 148-308 -45 0.299-0.324 Automatically fall off Smooth and beautiful Example 6 0.06 0.18 3.1 502 122-244 -50 0.342-0.382 Automatically fall off Smooth and beautiful Example 7 0.07 0.21 2.8 517 198-307 -44 0.255-0.345 Automatically fall off Smooth and beautiful Comparative Example 1 0.08 0.25 3.8 479 56-109 -20 0.243-0.236 Slightly sticky Undercut Comparative Example 2 0.07 0.43 6.8 504 15-95 -10 0.011-0.208 Bright Arc Irregular weld bead Comparative Example 3 0.05 0.32 5.6 502 35-115 -15 0.128-0.486 Sticky residue Undercut Comparative Example 4 0.08 0.48 3.2 485 38-188 -30 0.119-0.374 Some sticky residue Weld bead has slight undercut It can be seen from Table 3 that the weight percentages of some components in the fluxes of Comparative Examples 1 to 4 exceed the scope involved in the technical solution of the present invention. For example, in Comparative Example 1, the weight percentage of the HJ431 flux added in the flux is lower than the weight percentage determined in the flux of the present invention. In Comparative Example 2, no Mn iron alloy agent is added; in Comparative Example 3, the amount of HJ431 flux added is higher than the weight percentage determined in the present invention, and no Al deoxidizer is added; in Comparative Example 4, no TiO2 substance and Al deoxidizer are added to the flux. It can be seen from Table 5 that the fluxes in Comparative Examples 1 to 4 have at least one of the performance indicators lower than the standard design requirements, and the process performance of the weld is significantly reduced. For example, the impact toughness in Comparative Example 1 does not meet the standard requirements, and the process performance of the weld after welding cannot meet the requirements. The impact toughness value, CTOD fracture toughness value and inclusions in Comparative Examples 2, 3, and 4 have certain excess phenomena, and all cannot meet the standard requirements. Therefore, the fluxes in Comparative Examples 1 to 4 are not suitable for the application requirements of pipes for hydrogen transport media.
[0033] It can be seen from Table 5 that, compared with Comparative Examples 1 to 4, the tensile strength of the weld after welding with the submerged arc sintering flux in Examples 4 to 7 is 485 to 517 MPa, the moisture content in the flux is less than 0.1%, the mechanical inclusions in the flux is less than 0.3%, the impact energy of the -10°C girth weld is ≥100 J, and the toughness transition temperature is below -40°C, the -10°C CTOD fracture toughness σm is ≥0.254 mm, and the diffusible hydrogen content is significantly lower than 4 ml / 100 g. At the same time, the slag shell can be automatically detached after welding with several fluxes, and the smooth and beautiful surface of the weld can be ensured. Therefore, the pipeline steel pipe for hydrogen medium transportation using the flux in Examples 4 to 7 has higher strength, high toughness and excellent fracture resistance, especially the weld morphology after welding has been significantly improved compared with the ordinary flux, and the various performances are much better than the current similar products. The present invention can meet the requirements of submerged arc welding of pipeline steel pipe for hydrogen medium transportation.
[0034] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A sintered flux suitable for hydrogen transport submerged arc welding of steel pipes, characterized in that: The chemical composition of the sintered flux is as follows by weight percentage: HJ431 welding powder: 40-50%, MgO: 10-15%, CaF2: 15-20%, BaCO3: 5-10%, TiO2: 2-5%, Al powder deoxidizer: 1-3%, Mn-Fe alloying agent: 5-10%, P<0.02%, S<0.018%.
2. According to claim 1, a sintered flux for hydrogen transport submerged arc welding steel pipe, characterized in that: The particle size of the HJ431 welding powder is 80-100 meshes, and the MnO content in the HJ431 welding powder is more than 40%; the CaF2 is added in the form of fluorite mineral powder, the particle size of the fluorite mineral powder is more than 100 meshes, and the CaF2 content of the fluorite mineral powder is 98%; the MgO is added in the form of fused magnesia, the particle size of the fused magnesia is 80-100 meshes, and the MgO content of the fused magnesia is 99%; the TiO2 is added in the form of natural rutile, the particle size of the natural rutile is 80-100 meshes, and the TiO2 content of the natural rutile is 93%; the BaCO3 is added in the form of barium carbonate, the particle size of the barium carbonate is 100-120 meshes, and the BaCO3 content in the barium carbonate is 99.2%; the particle size of the Al powder deoxidizer is 60-80 meshes, and the Al content of the Al powder deoxidizer is 99%; the particle size of the Mn-Fe alloying agent is 60-80 meshes, The Mn content of the Mn-Fe alloy is 99%.
3. According to claim 2, a sintered flux for hydrogen transport submerged arc welding steel pipe, characterized in that: When the chemical components required for the sintering flux are added in the form of HJ431 welding powder, fluorite mineral powder, fused magnesia, natural rutile, barium carbonate, Al powder deoxidizer, and Mn-Fe alloying agent, the weight percentages of the mineral components and alloys in the sintering flux are: HJ431 welding powder: 40-50%, fluorite mineral powder: 12-24%, fused magnesia: 12-18%, barium carbonate: 7-12%, natural rutile: 2-5%, Al powder deoxidizer: 3-5%, and Mn-Fe alloying agent: 5-10%.
4. The sintered flux for hydrogen transport submerged arc welding steel pipe according to claim 1, characterized in that: The Mn-Fe alloying agent is an electrolytic Mn-Fe alloying agent.
5. The sintered flux for hydrogen transport submerged arc welding of steel pipes according to claim 1, characterized in that: The moisture content of the sintered flux is less than 0.1%, the mechanical inclusions in the sintered flux is less than 0.3%, the tensile strength of the weld welded by the sintered flux is 489∽524MPa, the impact energy of the girth weld at -10℃ is ≥119J, and the CTOD fracture toughness σ at -10℃ is m ≥0.2662mm, diffusible hydrogen content ≤3.77ml / 100g.
6. A method for preparing a sintered flux for hydrogen transport submerged arc welding steel pipe according to claim 1, characterized in that: The following steps are involved: S1: By weight, 40-50 parts of HJ431 welding powder, 12-18 parts of fused magnesia, 7-12 parts of barium carbonate, 18-24 parts of fluorite mineral powder, 2-5 parts of natural rutile, 3-5 parts of Al powder deoxidizer, and 5-10 parts of Mn-Fe alloying agent are uniformly mixed; S2: adding 15.48-31.5 parts of a binder to the mixture obtained in step S1, and vibrating and shaking the wet material formed by the bonding with a dustpan or a granulator to granulate; S3: During the granulation process, the particle size of the granulated flux is controlled between 10 and 60 meshes through a 10-20 mesh sieve; S4: drying the formed flux in a high temperature furnace at a temperature range of 200-350°C; S5: sintering the dried flux in a sintering furnace at a temperature range of 800-900°C; S6: The sintered flux is screened through 10~60 mesh and then packaged.
7. A method for preparing a sintered flux for hydrogen transport submerged arc welding steel pipe according to claim 6, characterized in that: The binder in step S2 is potassium sodium water glass, and the potassium sodium water glass as a binder has a Baume degree of 41.9-43.9 and a modulus of 2.5-2.7.
Citation Information
Patent Citations
High-alkalinity high-tenacity low-hydrogen agglomerated flux and preparation method thereof
CN102601544A
Ultralow diffusible hydrogen sintered flux used for welding low-temperature steel and preparation and application
CN108581273A
Sintered flux for hydrogen-resistant steel, preparation method of sintered flux, and deposited metal
CN112496596A
Method for manufacturing pipe tower type pylon for wind power generation
CN102371471A
Automatic submerged arc welding flux and preparation method thereof
CN102632349A